SHAME AND THE FIGURE OF THE FANGIRL: THE SOCIAL DYNAMIC OF SHAME IN POP MUSIC FANDOMS ONLINE - Samlal, Sascha Tanuja (AoIR Selected Papers of Internet Research, 2026)
Approaching shame from a queer theoretical framework, this paper will consider how the dynamic of shame operates within popular music fandoms online. Fangirls are subject to and participate in external and lateral shaming to enforce femmephobic ideals of normative femininity within fandom spaces. This leads to the derision of these fandoms, often labelled as ‘toxic’. However, shame is also used productively in these spaces – shame has been made a criterion of community bonding and shared intimacy between fangirls. Drawing on surveys and interviews, this paper aims to uncover how fangirls ultimately negate and rework experiences of shame through participation in pop music fandoms online, as this collective shame strengthens community ties and feelings of kinship among fangirls.